2019
DOI: 10.1002/cbdv.201900416
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal Activity of Essential Oils from Cinnamomum cassia against the Pathogenic Fungi of Panax notoginseng Diseases

Abstract: The frequent disease of Panax notoginseng caused by the pathogenic fungi in field cultivation has become the major threaten to the sustainable development of it. The present study was conducted to find natural agent with potential inhibition against pathogen. Therefore, the inhibitory effects of Cinnamomum cassia (L.) J.Presl essential oils (EOs) against P. notoginseng associated pathogenic fungi were conducted both in vitro and in vivo experiments. The results of the Oxford cup test revealed that C. cassia dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…vulgare populations from the Asian area have been poorly explored. In addition, many kinds of EOs, such as Cinnamomum cassia ( Ma et al, 2019 ), Litsea cubeba ( Yang et al, 2010 ) and Zanthoxylum leprieurii ( Tanoh et al, 2020 ), etc., have also great potential in the control of plant disease. Moreover, the researches on Origanum EOs and its main components against plant pathogens mainly focus on the antimicrobial activities ( De Martino et al, 2009a ; Stefanakis et al, 2013 ), while the mechanism of antifungal action is still unclear and the actual application is also necessary to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…vulgare populations from the Asian area have been poorly explored. In addition, many kinds of EOs, such as Cinnamomum cassia ( Ma et al, 2019 ), Litsea cubeba ( Yang et al, 2010 ) and Zanthoxylum leprieurii ( Tanoh et al, 2020 ), etc., have also great potential in the control of plant disease. Moreover, the researches on Origanum EOs and its main components against plant pathogens mainly focus on the antimicrobial activities ( De Martino et al, 2009a ; Stefanakis et al, 2013 ), while the mechanism of antifungal action is still unclear and the actual application is also necessary to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Cavalcanti and Almeida (10), the oil of this species demonstrated antifungal activity against strains of Candida albicans isolated from HIV positive patients and standard strain (ATCC 76845), with a MIC value of 64 μg/mL being observed for the most part of the strains analyzed. MA et al (9), have already proved the antifungal property of C. cassia oil against pathogenic fungi present in Panax notoginseng, a plant widely used in traditional Chinese medicine. Research specifically focused on the action of cinnamaldehyde has shown action against Malassezia pachydermatis with MIC of up to 2.5 µg/mL (44) and against clinical isolates of Candida resistant to fluconazole, presenting MIC of 90 up to 100 µg/mL (45).…”
Section: Resultsmentioning
confidence: 99%
“…It has already been found that the same essential oil can present different antifungal activity and mechanism of action when it is tested against different pathogens (54,55). Such a result may be associated with the complexity and diversity of antifungal mechanisms (9). According to studies in the field, the mechanism of antifungal action of the Cinnamomum cassia essential oil may be associated with the CHO group present in the molecule of the cinnamaldehyde.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations